Factors that affect human longevity - Bolin, Traci (Kansas State University, 2017)
Longevity, and factors that may increase the human lifespan, have been the topic of many research studies attempting to pinpoint direct positive influences. Research demonstrates that among those who live beyond an average life expectancy, approximately 25% of the increased lifespan is related to genetics. The remaining 75% is largely due to environmental factors, mainly diet and lifestyle factors, that have the ability to influence genetic effects for increased longevity. The following types of studies on diet and lifestyle factors for increasing longevity and decreasing the incidence of chronic conditions were reviewed: Prospective cohorts, longitudinal, in vitro, randomized controlled trials, and prospective case-controlled studies. Results related to the Mediterranean Diet were consistent in the conclusion that adherence to this diet increased the lifespan and delayed the development of chronic conditions although calorie restriction demonstrated an increase in longevity, the studies examined failed to correlate this diet to the reduced incidence of disease development. Red meat and alcohol consumption, though both are considered carcinogenic, demonstrated some benefits to the elderly. However, both need to be consumed with caution as they may negatively impact health when consumed outside of moderation. Physical activity demonstrated a consistent benefit to the elderly by increasing longevity and decreasing age-related conditions. Epigenetic research consistently concluded that a diet high in antioxidants and healthy fats both increase telomere length and decrease DNA damage though the exact mechanism remains unknown. Studies on the impact of regular social interactions and time spent on leisure activities in advanced age are consistent in the conclusion that both contribute to health and well-being in this demographic group, but failed to connect to an increase in longevity.
Keywords: Longevity